A comparison of airway devices for the simulated entrapped patient - Pap, Robin (My University, 2012)
Introduction: Control over the patient bears time-critical importance in emergency medicine. In the entrapment situation after a Motor Vehicle Collision (MVC), emergency care including airway management may need to be initiated before extrication and thus with restricted access. Objective: This manikin study aimed at answering the question of which advanced airway device can be inserted the fastest and most reliably by paramedics in the simulated entrapped patient. Methods: Paramedics were asked to insert four airway devices (endotracheal tube with the Macintosh laryngoscope, endotracheal tube with the Airtraq® optical laryngoscope, Laryngeal Mask Airway - SupremeTM, and Laryngeal Tube Suction - DisposableTM) in randomised order into a manikin seated in the driver seat of a light motor vehicle. Time to first successful ventilation and number of attempts required for successful insertion were measured. Following each insertion, participants were asked by means of a questionnaire to rate the degree of insertion difficulty (scale 1 – 10) and provide reasons for this rating. Finally, participants were asked which device they preferred and why. Results: Prospectively collected data from 26 paramedics were analysed. The LMA-SupremeTM had the shortest mean time to first successful ventilation (16.7 seconds (CI [0.95]; 14.9 - 18.6)), followed by the LTS-DTM (19.4 seconds (CI [0.95]; 18.0 - 20.8)), ETI using the Macintosh laryngoscope (37.7 seconds (CI [0.95]; 31.8 - 43.5)) and ETI using the Airtraq® (41.2 seconds (CI [0.95]; 36.7 - 45.6)). Both face-to-face ETI with the Macintosh laryngoscope and the insertion of the LMA-SupremeTM had 100% first-attempt success. Five participants required a second attempt to successfully intubate the manikin using the Airtraq® and one participant had to re-insert the LTS-DTM for correct placement. In terms of insertion difficulty, the LMA-SupremeTM received the lowest mean score (1.7/10 (CI [0.95]; 1.2 - 2.1)) followed by the LTS-DTM (2.5/10 (CI [0.95]; 1.8 – 3.2)), face-to-face ETI using the Macintosh laryngoscope (3.7/10 (CI [0.95]; 2.9 - 4.5)), and ETI with the Airtraq® (4.5/10 (CI [0.95]; 3.7 - 5.3)). Most participants chose the Macintosh laryngoscope for ETI as their preferred device (10/26; 38%) followed closely by the LMA-SupremeTM (9/26; 35%). These participants stated clinical experience and ease of insertion respectively as the primary reasons for their preference. Conclusion: Besides ETI, Supraglottic Airway Devices are beneficial alternative airway devices to be considered by paramedics in the entrapped patient after a MVC. The LMA-SupremeTM was the fastest and least difficult airway device to insert. Face-to-face endotracheal intubation with the Macintosh laryngoscope remains an important definitive airway that was shown to be performed competently by participating paramedics. The Airtraq® can be used for face-to-face ETI and enables improved laryngoscopy.
A research report submitted in partial fulfilment of the requirements for the degree Master of Science in Medicine in the Field of Emergency Medicine in the Division of Emergency Medicine, University of the Witwatersrand
Keywords: prehospital emergency medicine; airway; medical rescue; entrapment-trauma; face-to-face endotracheal intubation; Airtraq; Laryngeal Mask Airway - Supreme; Laryngeal Tube Suction - Disposable; Airway Obstruction--therapy; Intubation, Intratracheal--methods; Respiratory Therapy--methods